Changes in Patient Characteristics and Practice Outcomes of a Tele-Urgent Care Clinic Pre- and Post-COVID-19 Telehealth Policy Expansions. - Khairat, Saif; Yuxiao Yao; Coleman, Cameron; McDaniel, Philip; Edson, Barbara; Shea, Christopher M. (Perspectives in Health Information Management)
Introduction The coronavirus 2019 pandemic (COVID-19) has resulted in major changes in lifestyle practices and healthcare delivery. The goal of this study was to examine changes in practice and service outcomes in a telehealth program before and after the federal and private telehealth policy expansion during the COVID-19 pandemic. These findings are particularly useful to understand what may be needed to overcome telehealth challenges in future disasters. Methods We conducted a cross-sectional analysis of virtual visits through a statewide telehealth center embedded in a large academic healthcare system. Primary outcomes of this study were changes in telehealth visits pre- and post-policy expansions among at-riskpopulations. Results A total of 2,132 telehealth visits were conducted: 1,530(71.8 percent) patients were female, 1,561(73.2 percent) were between the ages 18-50, 1,576(74 percent) were uninsured, and 1,225(57.5 percent) were from rural regions. The average number of telehealth visits per day increased from 14 to 33 visits post-expansion. A significant change in patient characteristicswas found among senior, uninsured, and rural patients after the telehealth expansion. There was an 11 percent decrease in telehealth visits from very high vulnerability regions postexpansion compared to pre-expansion. There was a 15 percent decrease in visits resulting in prescription post-expansion (p-value<0.01). Conclusions COVID-19 policy expansions expanded telehealth utilization among at-riskpopulations such as senior, uninsured, and rural patients while decompressing hospitals and emergency rooms and maintaining positive patient experiences. Further regulations are needed around virtual visits unintended consequences, software certification, and guidelines for workforce training.